Organisational culture for information managers - Oliver, Gillian (Chandos Publishing, 2011)
"In today's digital environment the workplace is characterised by individuals creating information perhaps independently of formal systems, or establishing new systems without knowledge of information management requirements. This book explains and explores the concept of organisational culture, specifically within the domain of information management. It draws on the author's wide-ranging practical experience in different workplaces and uses research findings from cross-cultural studies of information management."--Publisher's website
Includes bibliographical references and index. - Online resource; title from PDF title page (EBSCO, viewed August 5, 2015)
Keywords: Corporate culture; Organizational change; Information technology -- Management; Culture organisationnelle; Changement organisationnel; Technologie de l'information; Gestion; Library, archive & information management; Organizational theory & behaviour; BUSINESS & ECONOMICS; Industrial Management; BUSINESS & ECONOMICS; Management; BUSINESS & ECONOMICS; Management Science; BUSINESS & ECONOMICS; Organizational Behavior; Libraries and Museums; Information technology; Management